Estimation of Familiarity and Popularity of Indian Celebrities-A “Q” Score Approach - Saini, Dimple; Kumar Dash, Sanjit (International Journal of Psychosocial Rehabilitation, 2020)
A colossal amount of money is being spent on celebrity endorsement worldwide by different business houses. It is also seen in the Indian scenario. The study is conducted with 20 Indian celebrities, which includes 10 cricketers and 10 Hindi film stars. The research paper is focused on exploring celebrity endorsement in India by finding out the ranking of celebrities in terms of familiarity and popularity among the consumers by applying the Q rating technique. The findings of this study will be of great help for business organizations to select appropriate celebrities for endorsing the brands.